PERAN GURU PAI DALAM MEMANFAATKAN MEDIA SOSIAL SEBAGAI SARANA PEMBELAJARAN DI ERA 4.0: (Studi Kasus di Sekolah Menengah Kejuruan Negeri 4 Bojonegoro) - Hamidatun Nihayah; Naili Risqi Mahbubah; M. Romadlon Habibullah (Pendidikan Agama Islam, 2021)
Teachers as agents of change, role models, social media as a medium and means of learning can create a pleasant learning atmosphere and motivate students to improve their abilities. They have competencies following the times. SMKN 4 Bojonegoro is a school that can apply internet-based learning and uses social media well, PAI subjects.Â This study aims to reveal the role of PAI teachers utilizing social media as learning in the era of 4.0 case studies at SMKN 4 Bojonegoro, about The implementation of PAI teachers in used social media as a learning tool in the 4.0 Era and the active role of teachers in utilizing social media as a learning tool in the 4.0 era. This study used a qualitative approach with a case study design, Data Collecting by using in-depth interviews, observation, and documentation techniques. Data analysis techniques include data reduction, data presentation, and concluding. Checking the validity of the findings is done by triangulation with various data, methods, and sources. The results showed that the implementation of PAI teachers in utilizing social media as a learning tool in the 4.0 era was by using WhatsApp and YouTube. Students get the PAI learning material itself and the latest PAI material. The active role of PAI teachers in utilizing social media as a learning tool in the 4.0 era is to become a subject, thereby guarding against radicalism and deviant beliefs. His efforts are to provide study materials for intolerant groups, inclusive religious practices and show wrong and radical sects and their dangers.